Scrotal absceso following an appendicitis - León Hernández Angélica; Palacios Acosta José Martín; Lezama Cordero Jaime Ricardo (Instituto Nacional de Pediatría, 2014)
Appendicitis is the most common cause of acute abdomen in children; approximately one third of all cases present with appendiceal perforation at the time of surgery. Some of postoperative complications in this condition are abscesses. In unusual places such as the scrotum however, for an intraabdominal event to cause a scrotal abscess, fluid displacement requires the presence of a patent processus vaginalis. We report the case of a child with perforated appendix followed by a scrotum abscess owing to a permeable vaginal canal. The abscess was and the patient wes and treatment was performed based triple scheme antibiotics, evolving satisfactorily. Key words: appendicitis, postoperative complications, residual abscess, inguinal canal.